2009
DOI: 10.1097/hjh.0b013e3283140c9e
|View full text |Cite
|
Sign up to set email alerts
|

CLCNKB-T481S and essential hypertension in a Ghanaian population

Abstract: Objective Prior to the discovery of CLCNKB-T481S there were no variants or clinical disorders associated with gain-of-function defects in thick ascending limb (TAL) of the kidney channels or transporters. CLCNKB-T481S is a novel gain-of-function variant that has been associated with essential hypertension. This finding has not been replicated until our current study. In this study we re-examine CLCNKB-T481S using a large homogenous population from Ghana, and coupled genetic analyses with the functional charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…Indeed, although with a large variation between ethnic populations [7][8][9][10], CLCNKA, CLCNKB and BSND are today proposed as candidate genes for hypertension [11,12]. Particularly, the common variant of ClC-Kb, T481S, shows greater chloride channel function than does wild-type ClC-Kb [13] and carriers of this variant show an increased systolic and diastolic pressure and increased likelihood of developing hypertension [14,15]. Four single-nucleotide polymorphisms within CLCNKA have been associated with salt-sensitive hypertension [16].…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, although with a large variation between ethnic populations [7][8][9][10], CLCNKA, CLCNKB and BSND are today proposed as candidate genes for hypertension [11,12]. Particularly, the common variant of ClC-Kb, T481S, shows greater chloride channel function than does wild-type ClC-Kb [13] and carriers of this variant show an increased systolic and diastolic pressure and increased likelihood of developing hypertension [14,15]. Four single-nucleotide polymorphisms within CLCNKA have been associated with salt-sensitive hypertension [16].…”
Section: Introductionmentioning
confidence: 98%
“…Subsequent studies performed on Australian, Swedish, Italian, and Japanese populations have failed to demonstrate a correlation between the ClC-Kb-T481S polymorphism and hypertension (Speirs et al, 2005;Kokubo et al, 2005;Fava et al, 2007;Barlassina et al, 2007). In contrast, Sile et al (2009) observed that ClC-Kb-T481S was associated with EH in males within the Ghanaian population; however, cultured mammalian cells that heterologously expressed ClC-Kb-T481S and the Barttin subunit did not perform significantly differently from the wild-type cells. In our study, we did not find an association between the ClC-Kb-T481S variant and essential hypertension in the Mongolian and Han populations.…”
Section: Renal Salt Reabsorption-related Gene and Hypertensionmentioning
confidence: 60%
“…The low blood pressure associated with defective ClC-Kb function suggests ClC-Kb is a target for antihypertensive drugs (41,81). This suggestion is further supported by the observation of an association between a common ClC-Kb polymorphism that increases channel activity and a predisposition to hypertension (7,37,62,73,126). However, it should be noted that such a predisposition has not been detected in all studies (17,37,73,132).…”
Section: Clc-ka/bmentioning
confidence: 69%
“…However, it should be noted that such a predisposition has not been detected in all studies (17,37,73,132). It has been suggested that salt-loading conditions as well as sex and ethic segregation need to be considered, and that larger studies are necessary to resolve the issue (73,126,150).…”
Section: Clc-ka/bmentioning
confidence: 92%